2019
DOI: 10.1111/ajd.13023
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and survival of Merkel cell carcinoma in New Zealand: A population‐based study between 2000 and 2015 with international comparison

Abstract: Background/Objectives: Merkel cell carcinomais an aggressive neuroendocrine skin cancer. Australian studies report high incidence and poor survival rates compared internationally. While New Zealand has a comparable UV index and racial composition to Australia, survival outcomes are currently unknown. The role of Merkel cell polyoma virus in oncogenesis of Merkel cell carcinoma is an active area of research. We describe the incidence and survival of Merkel cell carcinoma in New Zealand with correlation to demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Merkel cell carcinoma (MCC) is a neuroendocrine carcinoma of the skin with a poor prognosis. The survival rate of MCC varies significantly; population-based studies from New Zealand, Finland, and the United States revealed 5-year disease-specific survival rates of 45%, 59%, and 73%, respectively [ 1 , 2 , 3 ]. In most MCCs (approximately 80% of MCC tumors in the northern hemisphere), the genome of Merkel cell polyomavirus (MCPyV) is integrated in the tumor cell genome [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merkel cell carcinoma (MCC) is a neuroendocrine carcinoma of the skin with a poor prognosis. The survival rate of MCC varies significantly; population-based studies from New Zealand, Finland, and the United States revealed 5-year disease-specific survival rates of 45%, 59%, and 73%, respectively [ 1 , 2 , 3 ]. In most MCCs (approximately 80% of MCC tumors in the northern hemisphere), the genome of Merkel cell polyomavirus (MCPyV) is integrated in the tumor cell genome [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most MCCs (approximately 80% of MCC tumors in the northern hemisphere), the genome of Merkel cell polyomavirus (MCPyV) is integrated in the tumor cell genome [ 4 , 5 ]. Our group and others have previously identified several clinicopathological factors that negatively influence survival in MCC, such as tumor MCPyV-negativity, lack of tumor-infiltrating lymphocytes, male sex, larger primary tumor size, presence of lymph node or systemic metastasis at diagnosis, and immunosuppression [ 1 , 2 , 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 ]. Despite the generally poor survival of MCC, there is a significant proportion of patients in our Finnish population-based cohort who are still alive over a decade after the initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some types of cancer in Australia are the highest in the world: melanoma,26 keratinocyte and melanocyte 29. Australia and New Zealand together have the highest rates for Merkel cell carcinoma 30 31. A number of studies have focused on geographical or socioeconomic disparities in cancer care and survival 32–38.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoma virus negative MCCs are shown more likely to occur in sun exposed regions, and have a higher mutational burden including UV light signature mutations 22 . Poor survival rates from MCC have been demonstrated in New Zealand which is thought be linked to high UV exposure, fair skin type and lower rates of MCPyV positivity in this region 23 . Interestingly, the lower limbs were noted overall to be the second most common location for MCC development.…”
Section: Discussionmentioning
confidence: 99%